Roles of Pharmacist in Tuberculosis: A Narrative Review - Subedi , Sapana (Journal of Karnali Academy of Health Sciences, 2024)
Tuberculosis (TB) is a disease resulting from infection with bacteria known as, Mycobacterium tuberculosis. It usually affects the respiratory system. Pharmacists can significantly contribute to ensuring effective routes for the care of patients with tuberculosis. The objective of this narrative review is to identify the possible roles of different types of pharmacists (mainly industrial, hospital, community, and clinical pharmacists) in prevention, diagnosis, and treatment of tuberculosis. This review is divided into four sections: (1) role of pharmacists in tuberculosis medication management; (2) their role in tuberculosis patient support and education; (3) public health collaboration; and (4) role of the pharmacists in resource-limited settings. The first part of the review outlines the responsibilities undertaken by pharmacists in medication management, like dispensing, preventing drug-resistant TB, and promoting medication adherence. The second section describes role of pharmacists in counseling, and diagnosis. The third section includes public health responsibilities, including the prevention of TB transmission and involvement in DOTS (Directly Observed Therapy Short-Course). Finally, the role of pharmacists in settings with limited resources, such as in low- and middle-income countries and other roles are described, along with strategies to enhance the involvement of pharmacists in tuberculosis. Professional assistance, enhanced patient care in the public sector, and promotional efforts in the media could contribute to reinforcing the role of pharmacists in tuberculosis. For aligning with the WHO’s new End TB Strategy 2016–2035, health systems should consider utilizing pharmacists to improve tuberculosis identification, diagnosis, and treatment to prevent morbidity and mortality.